2018
DOI: 10.1111/vox.12734
|View full text |Cite
|
Sign up to set email alerts
|

Microchimerism in Ghanaian children recipients of whole blood transfusion for severe anaemia

Abstract: Background and objectives Transfusion‐acquired microchimerism (TA‐Mc) has been reported in major trauma but not in young children despite relative immunodeficiency who, in sub‐Saharan Africa, often suffer severe anaemia related to haemoglobinopathies or primary malaria infections. We examined the hypothesis that such massive red cell destructions might provide conditions favourable to TA‐Mc, particularly when exposed to massive amounts of parasite antigens. Materials and Methods Twenty‐seven female children <5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The incidence of vitiligo increases notably when patients are in a state of disease or poor physical condition [11,12]. Anemia can lead to low immunity and slow metabolism, and vitiligo, as a disease that is difficult to cure, has a high possibility of relapse [13,14]. Moreover, the history of vitiligo and anemia increases the risk of vitiligo relapse.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of vitiligo increases notably when patients are in a state of disease or poor physical condition [11,12]. Anemia can lead to low immunity and slow metabolism, and vitiligo, as a disease that is difficult to cure, has a high possibility of relapse [13,14]. Moreover, the history of vitiligo and anemia increases the risk of vitiligo relapse.…”
Section: Introductionmentioning
confidence: 99%
“…If, however, this hypothesis is correct, TA-MC may continue to occur in other populations of transfused trauma patients, as blood processing and leukoreduction methods vary considerably. However, in resource limited settings where leukoreduction is not performed due to cost and logistics, and particularly settings where fresh whole blood transfusions are routinely employed for trauma, young children with severe anemia, and other indications, TA-MC will likely continue to occur (as documented in a recent study from Ghana), 15 and hence continued studies are warranted of incidence and potential adverse or beneficially consequences of TA-MC.…”
Section: Discussionmentioning
confidence: 99%
“…This altered environment may be a key factor in enabling the establishment of persistent microchimerism. The one example of TA‐MC occurring outside of traumatic injury is from a recent study that found evidence of microchimerism in pediatric recipients of whole blood in Ghana . While the study was small and had some limitations, the finding is compelling and merits further study.…”
mentioning
confidence: 97%